Effect of Conservative Interventions for Musculoskeletal Disorders in Preprofessional and Professional Dancers: A Systematic Review - Justine Benoit-Piau; Christophe Benoit-Piau; Nathaly Gaudreault; Mélanie Morin (North American Sports Medicine Institute, 2023)
# Background Preprofessional and professional dancers are among the athletes who sustain the most musculoskeletal disorders. In recent years, conservative treatment and preventive measures have been investigated in this population. However, no systematic review regarding their effectiveness has been conducted. # Hypothesis/Purpose The aim of this systematic review was to locate, appraise and synthesize the available information on conservative interventions currently used for treating and preventing MSK disorders and their effect on pain and function in preprofessional and professional dancers. # Study design Systematic review. # Methods A systematic literature search was conducted using PubMed, CINHAL, ERIC, SportDiscus and Psychology and behavioral science collection. Prospective and retrospective cohort studies, as well as randomized and non-randomized controlled trials investigating conservative interventions for musculoskeletal disorders in preprofessional and professional dancers were included in this study. The main outcome measures included pain intensity, function, and performance. All included studies were evaluated for risk of bias using the Downs and Black checklist. # Results Eight studies were included in the review. These studies included ballet and contemporary dancers, as well as professional and preprofessional dancers. In total, the studies included 312 dancers, 108 male and 204 female. Studies had a risk of bias that ranged from poor (8/28) to good (21/28) on the Downs and Black checklist. The conservative interventions used included customized toe caps, dry-needling, motor imagery, and strength and conditioning programs. The use of customized toe caps, motor imagery and strength and conditioning programs had promising results regarding pain and function in dancers. # Conclusion In order to reach a solid conclusion, more quality studies are needed. The addition of control groups to studies, as well as multimodal interventions should be considered. # Level of Evidence I